The Influence of Nutritional Education and Reproductive Health of Pregnant Women on the Knowledge and Attitudes of Pregnant Women in Talun District Using a Quasi Experimental Study - Nena Bidari Putri; Shofa Nur Fauzah; Triono Adi Suroso (International Journal Labs, 2025)
The prevalence of SEZs in Indonesia was 35.5% in 2018. Data from West Java Province in 2020 reported 55,629 cases of pregnant women experiencing SEZs across 27 districts and cities in the province. Specifically, based on data from West Java Province, there were 4,696 cases of pregnant women experiencing SEZs in Cirebon Regency. The factor of knowledge about nutrition and reproductive health is related to the incidence of SEZs, which are a cause of fetal growth and development disorders. For this reason, this research was carried out. The research aims to determine the influence of nutrition education and reproductive health of pregnant women on the knowledge and attitudes of pregnant women in Talun District. This study is Quasi Experimental research with a Separate Sample Pretest-Posttest design. The population consisted of pregnant women undergoing antenatal care at the Talun Health Center, Cirebon Regency, West Java, totaling 32 respondents who met the inclusion criteria. Quota sampling was used as the sampling method. A T-test analysis was conducted to determine the influence of nutrition education and reproductive health of pregnant women on their knowledge and attitudes in Talun District. The T-test analysis found a significant influence of nutrition education and reproductive health of pregnant women on their knowledge and attitudes in Talun District (P < 0.05). The provision of nutrition and reproductive health education has a positive effect on improving the knowledge and attitudes of pregnant women.